2016
DOI: 10.3389/fnhum.2016.00387
|View full text |Cite
|
Sign up to set email alerts
|

Phase-Amplitude Coupling Is Elevated in Deep Sleep and in the Onset Zone of Focal Epileptic Seizures

Abstract: The interactions between different EEG frequency bands have been widely investigated in normal and pathologic brain activity. Phase-amplitude coupling (PAC) is one of the important forms of this interaction where the amplitude of higher frequency oscillations is modulated by the phase of lower frequency activity. Here, we studied the dynamic variations of PAC of high (gamma and ripple) and low (delta, theta, alpha, and beta) frequency bands in patients with focal epilepsy in different sleep stages during the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(110 citation statements)
references
References 68 publications
(103 reference statements)
8
101
0
Order By: Relevance
“…Ripples usually predominate during LVF, whereas fast ripples (FRs) are more frequent during PS seizures. 17 In our previous study, we demonstrated that in the interictal period, higher values of PAC exist in the SOZ compared to normal channels 13 ; however, how different types of epilepsy or seizures are associated with different coupling patterns has not been investigated yet. 7 Phase-amplitude coupling (the coupling between the amplitude of high-frequency activity and the phase of the lowfrequency band; PAC) has been the subject of many studies, not only in normal brain activity, but also in patients with epilepsy.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Ripples usually predominate during LVF, whereas fast ripples (FRs) are more frequent during PS seizures. 17 In our previous study, we demonstrated that in the interictal period, higher values of PAC exist in the SOZ compared to normal channels 13 ; however, how different types of epilepsy or seizures are associated with different coupling patterns has not been investigated yet. 7 Phase-amplitude coupling (the coupling between the amplitude of high-frequency activity and the phase of the lowfrequency band; PAC) has been the subject of many studies, not only in normal brain activity, but also in patients with epilepsy.…”
Section: Introductionmentioning
confidence: 95%
“…PS is associated with neuronal hypersynchronization, whereas LVF is associated with increased local neuronal firing due to either disinhibition or hyperexcitation. 13,14 The interaction of HFOs and slow waves can also help distinguish physiologic and pathologic HFOs. Ripples usually predominate during LVF, whereas fast ripples (FRs) are more frequent during PS seizures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One common type of cross-frequency coupling is phase-amplitude coupling (PAC) where the phase of a slower oscillation is correlated with the amplitude of a faster oscillation. The magnitude of PAC represents the putative interactions between underlying circuits which behave abnormally in models of focal epilepsy (Guirgis et al 2015;Amiri et al 2016;Edakawa et al 2016), but has not yet been evaluated in generalized epilepsies. Critically, PAC is a potentially useful metric as the correlation between different oscillatory EEG components may vary without overt changes in the power spectrum, and can therefore uniquely differ for similar power spectra.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has previously reported low frequency oscillation modulated high frequency oscillation can be used to successfully define ROI using intracranial recordings [26]. More recently, cross frequency coupling between high (gamma and ripple) and low (delta, theta, alpha, and beta) frequency rhythms was reported to be significantly stronger in the SOZ compared to normal regions in intracranial recording of deep sleep [60].…”
Section: Localization Of S Cfc Signal Can Guide the Placement Of Imentioning
confidence: 99%